2019
DOI: 10.3329/birdem.v9i3.43081
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in Bangladeshi subjects: a laboratory based study

Abstract: Background: Vitamin D plays important role in normal functioning of multiple organs of the body. Hypovitaminosis D is known to be prevalent worldwide including the tropical countries. The present study was carried out to evaluate the vitamin D status in Bangladeshi patients undergoing laboratory investigation for vitamin D. Methods: This was a laboratory-based study. Data were extracted from the database of a diagnostic centre of Dhaka city and were analysed. Vitamin D status was defined as follows: defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
5
2
Order By: Relevance
“…[ 19 ] Among the 212 study populations of different age groups, all were found to be vitamin D deficient in another study conducted by Hossain et al [ 20 ] Islam et al , in a laboratory-based study of 793 samples, found that 61.4% had vitamin D deficiency, and 24.1% had insufficiency, vitamin D level was found sufficient in 13.1% subjects. [ 25 ] In the current study, the frequency of hypovitaminosis D (72.6%, insufficiency 33.4%, and deficiency 39.2%) was lower than the previous observations. In the absence of vitamin D status of the general population of the country and lack of an otherwise healthy normal-weight control group in the current study, it is tough to comment on the relative status of vitamin D in our study subjects.…”
Section: Discussioncontrasting
confidence: 79%
“…[ 19 ] Among the 212 study populations of different age groups, all were found to be vitamin D deficient in another study conducted by Hossain et al [ 20 ] Islam et al , in a laboratory-based study of 793 samples, found that 61.4% had vitamin D deficiency, and 24.1% had insufficiency, vitamin D level was found sufficient in 13.1% subjects. [ 25 ] In the current study, the frequency of hypovitaminosis D (72.6%, insufficiency 33.4%, and deficiency 39.2%) was lower than the previous observations. In the absence of vitamin D status of the general population of the country and lack of an otherwise healthy normal-weight control group in the current study, it is tough to comment on the relative status of vitamin D in our study subjects.…”
Section: Discussioncontrasting
confidence: 79%
“…Most of the respondents had inadequate Vitamin D levels (36.5% had deficient and 46.2% had insufficient) which was consistent with the results found by Islam et al They found that 86% had hypovitaminosis D (61.4% had a deficiency and 24.1% had insufficiency). 8 But the prevalence rate of deficiency was more than expected in this study. The cause may be homebound due to the lockdown during covid pandemic period.…”
Section: Normality Of the Datasetcontrasting
confidence: 48%
“…Sample size: By using single proportion formula taking the prevalence of hypovitaminosis D as 86% in Bangladesh, 8 sample size was estimated as follows-…”
Section: Study Populationmentioning
confidence: 99%
“…We and others find a high incidence of VitD deficiency in Bangladesh [ 17 ]. Therefore, a second goal of these studies was to follow-up on our observations that VitD may modulate As immunotoxicity [ 15 ].…”
Section: Introductionmentioning
confidence: 99%